Speculative mean monthly temperatures in the Arctic (75 degrees N) stratosphere, 25 to 55 kilometers - Kantor, Arthur J.; Air Force Cambridge Research Laboratories (U.S.)
"Reprinted from the JOURNAL OF GEOPHYSICAL RESEARCH, Vol. 71, No. 10, pp. 2445-2450, 15 May 1966." Research supported by the Aerospace Instrumentation Laboratory, Air Force Cambridge Research Laboratories, Office of Aerospace Research, United States Air Force, L.G. Hanscom Field, Bedford, Massachusetts. Aerospace Instrumentation Laboratory Project 8624. "July 1966." Includes bibliographical references. Aerospace Instrumentation Laboratory Mode of access: Internet.